Design of AUVs based on 3D coils positioning and distributed base station control for nuclear spent fuel pools - Shen, Shijun; Chen, Jiaoyuan; Wang, Chaofan; Wang, Chenyang; Gong, Dawei (Frontiers in Energy Research, 2023)
An underwater magnetic induction positioning and communication system and an energy-efficient distributed control algorithm for underwater base stations are proposed in this paper. The positioning and communication system consists of a number of base stations and an Autonomous Underwater Vehicle (AUV) equipped with three-axis source coils respectively. The AUV receives this signal and based on its amplitude and phase information is able to locate the AUV and communicate with the base station. Due to the short positioning distance of magnetic induction positioning technology, a large number of base stations need to be installed underwater, which puts high demands on the control of the base stations. In this paper, an energy-efficient distributed control algorithm for underwater base stations is proposed to enable the AUV to meet the operational requirements while minimizing the total energy consumption of the base station. According to the simulation results, the design solves the problem that traditional underwater positioning and communication equipment cannot work stably for long periods of time in a high radiated environment, with a positioning error of no more than 10 cm within a preset operating range, and the algorithm proposed in this paper is able to reduce energy wastage by about 20%.